Hip adductor injury in competitive swimmers - Grote, K.; Lincoln, T. L.; Gamble, J. G. (The American Journal of Sports Medicine, 2004)
METHODS: The authors conducted a survey of 296 competitive swimmers to assess the incidence and importance of interfering groin pain in breaststroke swimmers. RESULTS: Breaststroke swimmers were more likely to have current groin pain (6.92%) than individual medley swimmers who did not compete in pure breaststroke events (0, P = 0.015). Breaststroke swimmers (42.7%) were also more likely than individual medley swimmers (21.5%, P = 0.000622) or nonbreaststroke, nonindividual medley swimmers (5.8%, P = 0.00000311) to have been unable to train breaststroke in practice during the past year due to groin injury. CONCLUSION: Results indicate that breaststroke swimmers are at significant risk of groin injury, groin injury is positively correlated with increased magnitude of breaststroke training, and groin injury may prevent participation in practices and competitions.